The Characterization of Biodegradable Plastics from Cassava Starch with Varried Addition of Robusta Coffee Skin (Coffea canefora) and Glycerol - Andrew Setiawan Rusdianto; Maghfirah Usman; Triana Lindriati; Eka Ruriani; Nidya Shara Mahardika (International Journal on Food, Agriculture and Natural Resources, 2022)
One of the solutions to the plastic pollution crisis is biodegradable plastic. The most efficient raw material for making biodegradable plastic is cassava starch, but it has a weakness in that natural fibers are generally added as reinforcement and natural filler. In this study, Robusta coffee skin fiber was used as a reinforcement for biodegradable plastic. To obtain the right variation of coffee skin composition, this study applied a completely randomized design (CRD) with two factors. The parameters observed in this study were thickness, water absorption, biodegradation, tensile strength, elongation, and modulus of elasticity. Data were analyzed using descriptive statistics and ANOVA test, coupled with the effectiveness index test was carried out. The results showed a thickness value of 0.703 – 1.007 mm. The value of water absorption is between 3.437 – 13.512 %. The resulting biodegradation value is between 32.914 – 68.971%. The tensile strength value is 19,056 – 46,507% and it is directly proportional to the modulus of elasticity, which is produced between 2.557 – 16.442 Mpa. The effectiveness index test demonstrated that the best treatments were obtained from the addition of 15% coffee skin with 20% glycerol, 10% glycerol with 20% coffee skin, and 5% glycerol with 20% coffee skin.